The effect of lenders' credit risk transfer activities on borrowing firms' equity returns - Ian W. Marsh (Bank of Finland, 2006)
Although innovative credit risk transfer techniques help to allocate risk more optimally, policy-makers worry that they may detrimentally affect the effort spent by financial intermediaries in screening and monitoring credit exposures.This paper examines the equity market's response to loan announcements.In common with the literature it reports a significantly positive average excess return – the well known 'bank certification' effect.However, if the lending bank is known to actively manage its credit risk exposure through large scale securitization programmes then the magnitude of the effect falls by two-thirds.The equity market does not appear to place any value on news of loans extended by banks that are known to transfer credit risk off their books.
URN:NBN:fi:bof-201501291021
Keywords: G12; G21; 330; bank loans; credit derivatives; bank certification